Nutritional and functional profile of carob bean (Ceratonia siliqua): a comprehensive review - Basharat, Zunaira; Afzaal, Muhammad; Islam, Fakhar; Hussain, Muzzamal; Ikram, Ali; Pervaiz, Muhammad Usama; Awuchi, Chinaza Godswill (International Journal of Food Properties, 2023)
Carob (Ceratonia siliqua) is one of Asia and Africa’s popular nutritional and medicinal crops. This unique plant has an outstanding functional properties and nutritional profile. Carob has high sugar content, drought resistance and is very economical. Carob fruit consists of pulp and seed that are rich sources of different bioactive components. Carob has wide applications in various industries (food, pharmaceuticals and cosmetics) as an anti-oxidant, thickener, stabilizer, lactic acid production and emulsions. The trend of moving toward natural products further highlights the use of carob in different fields due to its excellent nutritional and therapeutic profile. Carob bean gum is widely used in the food industry. The current review has highlighted the nutritional composition, bioactive profile, functional properties, and recent findings on the subject.
Keywords: Functional profile; Nutritional composition; Carob bean; Bioactive compounds